2018
DOI: 10.1007/s40820-018-0209-1
|View full text |Cite
|
Sign up to set email alerts
|

Bi Nanoparticles Anchored in N-Doped Porous Carbon as Anode of High Energy Density Lithium Ion Battery

Abstract: A novel bismuth–carbon composite, in which bismuth nanoparticles were anchored in a nitrogen-doped carbon matrix (Bi@NC), is proposed as anode for high volumetric energy density lithium ion batteries (LIBs). Bi@NC composite was synthesized via carbonization of Zn-containing zeolitic imidazolate (ZIF-8) and replacement of Zn with Bi, resulting in the N-doped carbon that was hierarchically porous and anchored with Bi nanoparticles. The matrix provides a highly electronic conductive network that facilitates the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 73 publications
(73 reference statements)
2
94
1
Order By: Relevance
“…When metallic Bi is formed again at the end of the 1st depotassiation process, its XRD peaks become slightly broader compared with that of the starting one, indicating that the metallic Bi nanodots do not agglomerate during the electrochemical cycling process due to the unique integrated nanostructure. This is very different from previous studies of Bi‐based anodes in lithium batteries, where fast Bi agglomeration is usually observed and results in poor cycling stability . Actually, all phases that appeared during potassiation/depotassiation (Bi, KBi 2 , K 3 Bi 2 , K 3 Bi) are nanoscale, which always ensures a short K + ionic transportation pathway.…”
Section: Resultscontrasting
confidence: 67%
“…When metallic Bi is formed again at the end of the 1st depotassiation process, its XRD peaks become slightly broader compared with that of the starting one, indicating that the metallic Bi nanodots do not agglomerate during the electrochemical cycling process due to the unique integrated nanostructure. This is very different from previous studies of Bi‐based anodes in lithium batteries, where fast Bi agglomeration is usually observed and results in poor cycling stability . Actually, all phases that appeared during potassiation/depotassiation (Bi, KBi 2 , K 3 Bi 2 , K 3 Bi) are nanoscale, which always ensures a short K + ionic transportation pathway.…”
Section: Resultscontrasting
confidence: 67%
“…Lithium-ion batteries (LIBs) are widely utilized in the portable electronics owing to their numerous merits, such as high energy density, long lifespan, and environmental friendliness [1][2][3][4]. Nevertheless, to meet the ever-growing demand for longer distance electric vehicles and more advanced electrical devices, the energy density of commercially available LIBs needs to be further enhanced [5][6][7]. Si anode with the highest theoretical specific capacity (4400 mAh g À1 ) presents the most competitive alternative to graphite among all the lithium storage materials [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The d ‐spacings of 2.45 and 2.60 Å are indexed to the (101) and (002) planes of ZnO, respectively, [ 30 ] whereas for metallic Zn, a d ‐spacing of 2.11 Å corresponding to the (101) plane is observed. [ 31 ] The distribution of ZnO on the surface of Zn@ZnO HPA was confirmed using energy‐dispersive X‐ray spectroscopy (EDS) (Figure S3, Supporting Information). A comparison of the oxygen components at the top, side, and bottom of Zn@ZnO HPA showed that the oxygen content decreased from the top to the bottom, which indicates that the thickness of the ZnO layer is dependent on the position, with the thickness generally decreasing from the top to the bottom.…”
Section: Resultsmentioning
confidence: 99%